The Triassic Mercia Mudstone Group: Sealing the UK's net zero future - Jonathon A. McEvoy; Richard H. Worden; Joshua Griffiths; Nicholas T. Smith; Daniel R. Faulkner; Samuel T.J. Jones; Holly J. Mills; Kevin G. Taylor (Earth-Science Reviews, 2026)

Amino acid and acylcarnitine profile of Aedes aegypti (L) post-blood feeding, after permethrin exposure, and during the life cycle - Mariana Lizbeth Jiménez-Martínez; Gerardo de Jesús Trujillo-Rodriguez; María de Lourdes Ramírez-Ahuja; Olga Karina Villanueva-Segura; Patricio Adrián Zapata-Morin; Griffith Samuel Lizarraga; Laura E. Martinez-de-Villarreal; Margarita L. Martinez-Fierro; Ivan Delgado-Enciso; Jose Ignacio Gonzalez-Rojas; Adriana E. Flores; Antonio Guzman-Velasco; et al. (Insect Biochemistry and Molecular Biology, 2025)

An island of receptor-like genes at the Rrs13 locus on barley chromosome 6HS co-locate with three novel sources of scald resistance - Peter E. Eckstein; Lindsay J. Griffith; Xiang M. Zhang; T. Kelly Turkington; Mark G. Colin; Samuel Holden; Sean Walkowiak; Gurcharn S. Brar; Aaron D. Beattie (Theoretical and Applied Genetics, 2024)

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

Relationship between coliphage and Enterococcus at southern California beaches and implications for beach water quality management - Amity G. Zimmer-Faust; John F. Griffith; Joshua A. Steele; Bryan Santos; Yiping Cao; Laralyn Asato; Tania Chiem; Samuel Choi; Arturo Diaz; Joe Guzman; David Laak; Michele Padilla; et al. (Water Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effect of carbohydrate–protein supplementation on endurance training adaptations - Abdullah F. Alghannam; Iain Templeman; Joel E. Thomas; Dawid Jedrzejewski; Samuel Griffiths; Joseph Lemon; Thomas Byers; Sue Reeves; Javier T. Gonzalez; Dylan Thompson; James Bilzon; Kostas Tsintzas; et al. (European Journal of Applied Physiology, 2020)
Purpose To examine the influence of post-exercise protein feeding upon the adaptive response to endurance exercise training. Methods In a randomised parallel group design, 25 healthy men and women completed 6 weeks of endurance exercise training by running on a treadmill for 30–60 min at 70–75% maximal oxygen uptake ( V O 2max ) 4 times/week. Participants ingested 1.6 g per kilogram of body mass (g kg BM −1 ) of carbohydrate (CHO) or an isocaloric carbohydrate–protein solution (CHO-P; 0.8 g carbohydrate kg BM −1 + 0.8 g protein kg BM −1 ) immediately and 1 h post-exercise. Expired gas, blood and muscle biopsy samples were taken at baseline and follow-up. Results Exercise training improved V O 2max in both groups ( p ≤ 0.001), but this increment was not different between groups either in absolute terms or relative to body mass (0.2 ± 0.2 L min −1 and 3.0 ± 2 mL kg −1 min −1 , respectively). No change occurred in plasma albumin concentration from baseline to follow-up with CHO-P (4.18 ± 0.18 to 4.23 ± 0.17 g dL −1 ) or CHO (4.17 ± 0.17 to 4.12 ± 0.22 g dL −1 ; interaction: p > 0.05). Mechanistic target of rapamycin (mTOR) gene expression was up-regulated in CHO-P (+ 46%; p = 0.025) relative to CHO (+ 4%) following exercise training. Conclusion Post-exercise protein supplementation up-regulated the expression of mTOR in skeletal muscle over 6 weeks of endurance exercise training. However, the magnitude of improvement in V O 2max was similar between groups.

Correction to: Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2019)

Signatures of genetic adaptation to extremely varied Australian environments in introduced European house sparrows - Samuel C. Andrew; Henrik Jensen; Ingerid J. Hagen; Sarah Lundregan; Simon C. Griffith (Molecular Ecology, 2018)
Due to its history of multiple introductions to novel environments worldwide, the house sparrow has been used as a model species to study local adaption in invasive avian species. New genomic resources such as a custom 200K SNP array and a house sparrow reference genome provide great prospects for studying rapid local adaptation in this invasive species. Here, we analyse high‐density genomewide genetic data collected across an extensive range of temperate, arid and tropical climates, in Australian populations that were introduced from Europe 150 years ago. We used two population differentiation ( PD ) and two ecological association ( EA ) methods to identify putative loci subject to selection across these varied climates. A majority of the outlier SNP s were identified through the use of the latent factor mixed models ( LFMM ) EA method, but the BayeScEnv EA method had the strongest overlap with the outliers from the two PD methods. Out of all the 971 outliers identified across the different methods, 38.3% were physically linked (within 20 kbps) to 575 known protein‐coding regions in the house sparrow reference genome. Interestingly, some outlier genes had been previously identified in genome scan studies of broadly distributed species or had strong links to traits that are expected to be important to local adaptation, for example, heat‐shock proteins, immune response and HOX genes. However, many outliers still have unknown relevance and some outliers can be false positives. Our results identify an opportunity to use the house sparrow model to further study local adaptation in an invasive species.

The genetic structure of the introduced house sparrow populations in Australia and New Zealand is consistent with historical descriptions of multiple introductions to each country - Samuel C. Andrew; Monica Awasthy; Peri E. Bolton; Lee A. Rollins; Shinichi Nakagawa; Simon C. Griffith (Biological Invasions, 2018)

Molecular diversity and distribution of eastern Atlantic and Mediterranean dogfishes Squalus highlight taxonomic issues in the genus - Ana Veríssimo; Diana Zaera‐Perez; Rob Leslie; Samuel P. Iglésias; Bernard Séret; Panagiotis Grigoriou; Aspasia Sterioti; Chrysoula Gubili; Claudio Barría; Clinton Duffy; Sebastián Hernández; Ioannis E. Batjakas; et al. (Zoologica Scripta, 2017)
The alpha taxonomy of the globally distributed shark genus Squalus has been under intense investigation recently, and many new species have been described over the last decade. However, taxonomic uncertainty remains about several taxa. Without consistent nomenclature and the ability to reliably distinguish between the different Squalus species, basic data collection, downstream conservation and management efforts are seriously compromised. To aid in clarifying the taxonomic status of Squalus species in the eastern Atlantic and Mediterranean, we assessed species diversity at the molecular level and evaluated the consistency in species identification in the region. Samples from all nominal Squalus species recognized in the above regions were collected in an international effort and sequenced for regions of the mitochondrial COI and ND 2 genes. These data were further analysed alongside publicly available sequences, including 19 of the 26 Squalus species globally recognized, to compare the regional genus‐level diversity with that found elsewhere. Our results confirm inconsistent species identification in the eastern Atlantic and Mediterranean Squalus , particularly concerning S. blainville and S. megalops , and reinforce the need to revise the status of S. megalops and S. mitsukurii as they may include several distinct species distributed around the world. The status of S. blainville is also discussed in the light of the current findings and its problematic taxonomic history.

Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2016)
Skates and rays constitute the most speciose group of chondrichthyan fishes, yet are characterised by remarkable levels of morphological and ecological conservatism. They can be challenging to identify, which makes monitoring species compositions for fisheries management purposes problematic. Owing to their slow growth and low fecundity, skates are vulnerable to exploitation and species exhibiting endemism or limited ranges are considered to be the most at risk. The Madeira skate Raja maderensis is endemic and classified as ‘Data Deficient’ by the IUCN, yet its taxonomic distinctiveness from the morphologically similar and more wide-ranging thornback ray Raja clavata is unresolved. This study evaluated the sequence divergence of both the variable control region and cytochrome oxidase I ‘DNA barcode’ gene of the mitochondrial genome to elucidate the genetic differentiation of specimens identified as R. maderensis and R. clavata collected across much of their geographic ranges. Genetic evidence was insufficient to support the different species designations. However regardless of putative species identification, individuals occupying waters around the Azores and North African Seamounts represent an evolutionarily significant unit worthy of special consideration for conservation management.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.